Legal System and Legal Culture in Japan - Kinoshita, Tsuyoshi (Zeitschrift für Japanisches Recht, 2001)
I. Problems Presented 1. Positivistic Approach versus Comparative Legal Culture 2. Analysis of a Non-Litigious Society 3. Is Japanese Law Part of the Civil Law System? 4. Methodology of Comparative Legal Culture II. The Old Stratum Of Japanese Legal Ideas 1. Indigenous Legal Ideas as Basso Ostinato of Japanese Law 2. Influence of Chinese and Indian Legal Cultures on Japanese Law 3. Influence of the European Civil Law System after the Meiji Restoration 4. Influence of American Law after World War II III. Japanese People’s Attitude towards Law 1. “Verrechtlichung” of the Traditional Japanese Society 2. Reception of German Legal Model in order to Keep Traditional Values 3. Japanisation of the Western Legal System by Extra-Legal Practices 4. Endorsement of Indigenous Values by Case Law IV. Conclusion 1. Cartesian Modern Western Law versus Postmodern Japanese Law 2. “Legal Culture” 3. “Legal System” and “Legal Family” 4. Japanese Law: “Westernized”, but not “Western Law”